Targeting B cell receptor signaling with ibrutinib in diffuse large B cell lymphoma - Wilson, Wyndham H; Young, Ryan M; Schmitz, Roland; Yang, Yandan; Pittaluga, Stefania; Wright, George; Lih, Chih-Jian; Williams, P Mickey; Shaffer, Arthur L; Gerecitano, John; de Vos, Sven; Goy, Andre; et al. (Nature medicine, 2015)
Clinical testing of BCR inhibition on DLBCL reveals determinants of response. The two major subtypes of diffuse large B cell lymphoma (DLBCL)—activated B cell–like (ABC) and germinal center B cell–like (GCB)—arise by distinct mechanisms, with ABC selectively acquiring mutations that target the B cell receptor (BCR), fostering chronic active BCR signaling 1 . The ABC subtype has a ∼40% cure rate with currently available therapies, which is worse than the rate for GCB DLBCL, and highlights the need for ABC subtype-specific treatment strategies 2 . We hypothesized that ABC, but not GCB, DLBCL tumors would respond to ibrutinib, an inhibitor of BCR signaling. In a phase 1/2 clinical trial that involved 80 subjects with relapsed or refractory DLBCL, ibrutinib produced complete or partial responses in 37% (14/38) of those with ABC DLBCL, but in only 5% (1/20) of subjects with GCB DLBCL ( P = 0.0106). ABC tumors with BCR mutations responded to ibrutinib frequently (5/9; 55.5%), especially those with concomitant myeloid differentiation primary response 88 ( MYD88 ) mutations (4/5; 80%), a result that is consistent with in vitro cooperation between the BCR and MYD88 pathways. However, the highest number of responses occurred in ABC tumors that lacked BCR mutations (9/29; 31%), suggesting that oncogenic BCR signaling in ABC does not require BCR mutations and might be initiated by non-genetic mechanisms. These results support the selective development of ibrutinib for the treatment of ABC DLBCL.